Pendidikan Perdamaian Bagi Pemuda Gereja - Berdinata Massang; Meryam A. Sabubu; Sry N. Umar (Tumou Tou, 2021)
This study aims to describe peace education for church youth at the Minahasa Evangelical Christian Church (GMIM) Talita Kum Amurang. This study uses descriptive qualitative research to describe the phenomenon based on the point of view of the informant. Data collection techniques were carried out by conducting interviews and observations based on interview guides. The instrument in this study was the researcher himself as the key instrument and used interview questionnaires that had been prepared. The data that has been obtained is then analyzed using the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that peace education was emphasized on positive values ​​based on the theological views of the Bible and Church theology in social life in society. Starting to be taught from an early age with appreciation and solving problems in the environment based on a comprehensive analysis and peace education with positive values ​​such as love, compassion, peace and gentleness which are interpreted according to the spiritual activities carried out by the church.